Rhizophora mangle, Red Mangrove - Natalia Medina Irizarry; Michael Andreu (EDIS)
This publication serves as an introduction to identifying Rhizophora mangle (red mangrove). A brief overview of the family, genus, species, common name, description, storm tolerance, threats, and applications are summarized. The target audience is Florida homeowners who live along the coast with an interest in native plant communities and conservation. The objective is to educate the public on the correct identification, value, and benefits of red mangroves.